Ladarixin, an inhibitor of the interleukin‐8 receptors CXCR1 and CXCR2, in new‐onset type 1 diabetes: A multicentre, randomized, double‐blind, placebo‐controlled trial - Piemonti, Lorenzo; Keymeulen, Bart; Gillard, Pieter; Linn, Thomas; Bosi, Emanuele; Rose, Ludger; Pozzilli, Paolo; Giorgino, Francesco; Cossu, Efisio; Daffonchio, Luisa; Goisis, Giovanni; Ruffini, Pier Adelchi; et al. (Diabetes, obesity & metabolism, 2022)
Aim To evaluate the ability of ladarixin (LDX, 400 mg twice‐daily for three cycles of 14 days on/14 days off), an inhibitor of the CXCR1/2 chemokine receptors, to maintain C‐peptide production in adult patients with newly diagnosed type 1 diabetes. Materials and Methods A double‐blind, randomized (2:1), placebo‐controlled study was conducted in 45 males and 31 females (aged 18‐46 years) within 100 days of the first insulin administration. The primary endpoint was the area under the curve (AUC) for C‐peptide in response to a 2‐hour mixed meal tolerance test (AUC[0‐120 min]) at week 13 ± 1. Secondary endpoints included C‐peptide AUC(15‐120 min), HbA1c, daily insulin requirement, severe hypoglycaemic events (SHE), the proportion of subjects achieving HbA1c less than 7.0% without SHE and maintaining a residual beta cell function. Follow‐up assessments were scheduled at weeks 13 ± 1, 26 ± 2 and 52 ± 2. Results In total, 26/26 (100%, placebo) and 49/50 (98%, LDX) patients completed week 13. The mean change from baseline to week 13 in C‐peptide AUC(0‐120 min) was −0.144 ± 0.449 nmol/L with placebo and 0.003 ± .322 nmol/L with LDX. The difference was not significant (0.149 nmol/L, 95% CI −0.04 to 0.33; P = .122). At week 26, the proportion of patients with HbA1c less than 7.0% without SHE was transiently higher in the LDX group (81% vs. 54%, P = .024). Otherwise, no significant secondary endpoint differences were noted. Transient metabolic benefit was seen at week 26 in favour of the LDX group in the prespecified subpopulation with fasting C‐peptide less than the median value at screening. Conclusions In newly diagnosed patients with type 1 diabetes, short‐term LDX treatment had no appreciable effect on preserving residual beta cell function.